2008
DOI: 10.1002/art.23600
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation‐associated insulin resistance: Differential effects in rheumatoid arthritis and systemic lupus erythematosus define potential mechanisms

Abstract: Objective. Insulin resistance is increased by inflammation, but the mechanisms are unclear. The present study was undertaken to test the hypothesis that decreased insulin sensitivity is differentially associated with mediators of inflammation by studying 2 chronic inflammatory diseases of different pathogenesis, systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA).Methods. We measured fasting insulin, glucose, and lipid levels, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
143
1
19

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 211 publications
(171 citation statements)
references
References 44 publications
(58 reference statements)
8
143
1
19
Order By: Relevance
“…Because 30% of our SLE patients were using PRED, this could have contributed to the higher IR observed in this group. We did not observe any correlations between current dose of PRED and markers of insulin sensitivity, which is in line with previous studies, showing no association between corticosteroid intake and HOMA IR (7,15,38). However, the insulinogenic index, which takes into account the insulin response 30 minutes after food intake, was positively correlated with current PRED dose in the SLE group.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Because 30% of our SLE patients were using PRED, this could have contributed to the higher IR observed in this group. We did not observe any correlations between current dose of PRED and markers of insulin sensitivity, which is in line with previous studies, showing no association between corticosteroid intake and HOMA IR (7,15,38). However, the insulinogenic index, which takes into account the insulin response 30 minutes after food intake, was positively correlated with current PRED dose in the SLE group.…”
supporting
confidence: 91%
“…SLE patients, even with mild disease, show higher levels of inflammatory cytokines (13). However, although 1 study has observed an association between circulating inflammatory cytokines and IR in SLE patients with mild disease (14), others have not confirmed this finding (2,15).…”
Section: Introductionmentioning
confidence: 99%
“…These processes are closely related: if insulin sensitivity decreases, a healthy beta cell will respond by augmenting insulin secretion, to prevent hyperglycemia (3). In RA patients, impaired insulin sensitivity, as assessed in the fasting state using the homeostatic model assessment of insulin resistance (HOMA-IR), has been reported, and this was associated with measures of disease activity and plasma levels of inflammatory proteins, including C-reactive protein (CRP), tumor necrosis factor ␣, and interleukin-6 (4,5).…”
mentioning
confidence: 99%
“…Оба варианта формирования патологического состояния являются равноверо-ятными. Так, например, было показано, что ин-сулинорезистентность развивается у пациентов с системной красной волчанкой и ревматоидным артритом [6]. Вместе с тем, появляется все больше данных в пользу того, что СД 2-го типа в отсут-ствие клинических проявлений какой-либо ауто-иммунной патологии сопровождается изменени-ем функционирования Т-и В-лимфоцитов [9,10].…”
Section: результатыunclassified